Sosialisasi dan Promosi Penggunaan Protokol Kesehatan dan Vaksinasi di Masa Pandemi Covid-19 - Aprillia D.F. Yapen; Ajeng M.P. Lestari; Dirk Orboi; Dita A. Khotimah; Eka Febri Rahmawati; Petra Pattipeilohy; Rosdiana Howay; Sarce M. Sasari; Sepdianti Pebiola; Tiara A. Nadapdap; Vinexa Alwendzani; Winda A. Aritonang; Dirk Y.P. Runtuboi; Agnes E. Maryuni (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
The COVID-19 outbreak has spread to all parts of the world, one of which is Indonesia. This COVID-19 virus has claimed many lives, not only claimed lives, this virus also claimed the happiness and economy of the community. The spread of the virus is very fast on March 2, 2020. The purpose of this activity is to provide information about vaccinations and to invite residents to comply with health protocols and be willing to be vaccinated. The results obtained from this activity are in the form of a short 5 minute video film with the theme about the flow of vaccination services and in the form of direct socialization of health protocols and vaccinations to the target community.Keyword: health protocols; vaccination; COVID-19, Socialization